Empirical Analysis of Poor Public Financial Management in Nigeria: Causes, Implications and Remedies - Rafindadi, Abdulkadir Abdulrashid; Ogidan, Olashinde Joseph (Asian Development Policy Review, 2018)
The study looks at the causes and economic implication of public sector decay with the aim to establish the relationship that sub-exist between public sector decay, the causes and it economic implication in Nigeria. Primary sources were employed in gathering data. A well-structured questionnaire of four sections was given to three hundred (300) respondents, out of which two hundred and seventy-three (273) of the questionnaires were retrieved. Descriptive statistics, Pearson product moment correlation and multiple regressions, using SPSS 23 version were used in analysing data. The study indicate that a unit increase in corruption, poor public financial management, institutional problem, staff absenteeism/ late coming to work, leaking and/or abuse of government information and lack of political will creates public sector decay in Nigeria by about 41.5%, 47.0%, 22.6%, 36.1%, 49.8% and 22.3% respectively. Similarly, the study further discovered that a unit reduction in the accessibility of basic equipment/facilities will worsen Nigeria economy by about 82.5%. These findings imply that they will tend to discourage investors, reduce the standard of living, and slow down economic development through wasteful spending among others. It is therefore recommended that government should implement policies that will strengthen PFM in Nigeria, such as GIFMIS which allow central control of public finances, IPPIS and TSA that block the revenue leakages.